Mind mapping Approach in Learning History - Dhiyauddin, Akmal; Ahmad, Suzana; Ismail, Marina; Mat Diah, Norizan (International Journal of Engineering and Technology, 2018)
Currently, most Malaysian teenagers know very little about Islamic history and its civilizations.  Although Islamic history and civilizations are covered briefly in Malaysian school syllabus, appreciation towards the subject is very little.  This is because of traditional approach of learning Islamic history does not appealing enough for the students to enjoy and understand the subject matter.  The capability of new powerful multimedia tools have enable an improved applications to be developed in order to facilitate a better teaching and learning environment.  Nevertheless, anticipation of mental abilities is also significant to engage a better learning process.  Due to this matter, a ‘Mind Mapping’ approach along with the theoretical foundations of teaching and learning tasks are studied and adapted in the Islamic History courseware development. The developed courseware was tested with (n=10) for its effectiveness and user experience.  The outcome yielded positive results based on the unique and interesting design.